Schur Algebras over C*-Algebras - Pachara Chaisuriya; Sing-Cheong Ong; Sheng-Wang Wang (International Journal of Mathematics and Mathematical Sciences)
Let 𝒜 be a C*-algebra with identity 1, and let s(𝒜) denote the set of all states on 𝒜. For p,q,r∈[1,∞), denote by 𝒮r(𝒜) the set of all infinite matrices A=[ajk]j,k=1∞ over 𝒜 such that the matrix (ϕ[A[2]])[r]:=[(ϕ(ajk*ajk))r]j,k=1∞ defines a bounded linear operator from ℓp to ℓq for all ϕ∈s(𝒜). Then 𝒮r(𝒜) is a Banach algebra with the Schur product operation and norm ‖A‖=sup{‖(ϕ[A[2]])r‖1/(2r):ϕ∈s(𝒜)}. Analogs of Schatten's theorems on dualities among the compact operators, the trace-class operators, and all the bounded operators on a Hilbert space are proved.